A detailed radio study of the energetic, nearby, and puzzling GRB 171010A. Issue 2 (12th April 2019) - Bright, J S; Horesh, A; van der Horst, A J; Fender, R; Anderson, G E; Motta, S E; Cenko, S B; Green, D A; Perrott, Y; Titterington, D
ABSTRACT: We present the results of an intensive multi-epoch radio frequency campaign on the energetic and nearby GRB 171010A with the Karl G. Janksy Very Large Array and Arcminute Microkelvin Imager Large Array. We began observing GRB 171010A a day after its initial detection, and were able to monitor the temporal and spectral evolution of the source over the following weeks. The spectra and their evolution are compared to the canonical theories for broad-band GRB afterglows, with which we find a general agreement. There are, however, a number of features that are challenging to explain with a simple forward shock model, and we discuss possible reasons for these discrepancies. This includes the consideration of the existence of a reverse shock component, potential microphysical parameter evolution, and the effect of scintillation.